Perisian Pemodelan Maklumat Bangunan (BIM) yang digunakan oleh Pemain Industri Pembinaan - Zuraidi, Farisha Aqillah; Yahya, Mohd Yamani (Research in Management of Technology and Business, 2024)
The construction industry is one of the fastest growing industries because skyscrapers are in higher demand. Real estate values ​​are increasing and this is why construction companies are now working on eco-friendly designs that take up less space but provide more amenities in an affordable price range. To make all this happen, it is very important to have a proper management system. With the use of technology and combined with better management, now everything has become easier. A simple but very effective step in this regard is to use building information modeling or BIM. The problem with this study is that a large number of individuals are not aware of the benefits of BIM and they only think it is a technology or a 3D form that is planned before construction. However, BIM is more than just 3D pictures, it is a model accompanied by a digital description that addresses the physical project. The main objective of the study is to identify the BIM software used by construction industry players. The study respondents consisted of players in the construction industry in Selangor. The research conducted is quantitative by using questionnaire instruments. The data obtained was analyzed using the Statistical Package for Social Science (SPSS) software version 27.0. The results of the study found that the BIM software that is often used is Autodesk AutoCAD and Autodesk Revit. Therefore, the results of this study will benefit construction industry players, students involved in construction and graduates before entering the world of work regarding useful BIM software.